Effect of pH and Gastrointestinal Enzymes on Stability of Psoralen, Bakuchicin and Bakuchiol using Simultaneous TLC Densitometric Method and Standardization of commercial formulations containing Psoralea cordyfollia Linn. - Chopade, Jyotsna Rudrakumar; Mahadik, Kakasaheb R.; Sathiyanarayanan, L.; Nikam, Ajinkya (Journal of Drug Delivery and Therapeutics, 2019)
Psoralea corylifolia is used for treatmet of skin diseases such as psoriasis, vitiligo. Psoralen is responsible for its effectiveness against psoriasis. Bakuchicin and Bakuchiol are DNA polymerase and topoisomerase II inhibitors. To study the effect of pH and gastrointestinal (GI) enzymes on Psoralen, Bakuchicin and Bakuchiol from Psoralea corylifolia Linn using a simple, sensitive, accurate and robust high performance thin layer chromatographic (HPTLC) method. The method was performed on silica gel 60 F254with n- Hexane : Ethyl acetate ( 7.5 : 2.5 v/v)  as the mobile phase. Densitometric scanning at 285 nm for Psoralen, Bakuchicin and Bakuchiol was used. The method was validated as per the guidelines of International Conference on Harmonization (ICH). In addition the applicability of the method was tested for the standardization of both mono and polyherbal formulations containing the above markers. The Rf values of 0.37, 0.48 and 0.63 were obtained for Psoralen, Bakuchicin and Bakuchiol respectively. The linearity range of 20-120 ng spot-1,  20-120 ng spot-1 and 80-280 ng spot-1  with good correlation coefficients of r2 = 0.998, 0.998 and 0.999 were obtained for Psoralen, Bakuchicin and Bakuchiol  respectively. The method was applied for the in vitro stability studies of above markers in simulated gastric and intestinal fluids to study the effect of pH and GI enzymes. Psoralen was found to be most stable in the simulated physiological fluids whereas other two compounds showed instability. The method was found to be precise, robust and suitable for the routine quality control analysis of plant extracts and polyherbal formulations.Keywords: Psoralea corylifolia Linn, Leguminoceae, HPTLC, Enzymatic stability